Definition of a new (Doniach‐Sunjic‐Shirley) peak shape for fitting asymmetric signals applied to reduced graphene oxide/graphene oxide XPS spectra. (18th October 2021) - Moeini, Behnam; Linford, Matthew R.; Fairley, Neal; Barlow, Anders; Cumpson, Peter; Morgan, David; Fernandez, Vincent; Baltrusaitis, Jonas
Abstract : The existence of asymmetry in X‐ray photoelectron spectroscopy (XPS) photoemission lines is widely accepted, but line shapes designed to accommodate asymmetry are generally lacking in theoretical justification. In this work, we present a new line shape for describing asymmetry in XPS signals that is based on two facts. First, the most widely known line shape for fitting asymmetric XPS signals that has a theoretical basis, referred to as the Doniach‐Sunjic (DS) line shape, suffers from a mathematical inconvenience, which is that for asymmetric shapes the area beneath the curve (above the x‐axis) is infinite. Second, it is common practice in XPS to remove the inelastically scattered background response of a peak in question with the Shirley algorithm. The new line shape described herein attempts to retain the theoretical virtues of the DS line shape, while allowing the use of a Shirley background, with the consequence that the resulting line shape has a finite area. To illustrate the use of this Doniach‐Sunjic‐Shirley (DSS) line shape, a set of spectra obtained from varying amounts of graphene oxide (GO) and reduced GO on a patterned, heterogeneous surface are fit and discussed.